Frequency of Sapheno-Femoral Junction and Sapheno-Popliteal Junction Incompetence on Duplex Ultrasonography in Patients with Varicose Veins - Rauf, Muhammad Haris; Slehria, Atiq-Ur-Rehman; Qasmi, Imran Masoud; Saleem, Sultan; Sohail, Marium (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine frequency of sapheno-femoral junction (SFJ) and sapheno-popliteal junction (SPJ) incompetence on duplex ultrasonography in patients with varicose veins.Study Design: Cross-sectional study.Place and Duration of Study: Shaikh Khalifa Bin Zayed Al-Nahyan/Combined Military Hospital, Rawalakot, Azad Jammu & Kashmir, from Aug 2019 to Feb 2020.Methodology: A total of 70 patients were selected using non-probability, consecutive sampling. After ethical approval, informed consent and relevant history taking, duplex ultrasonography (DUS) was done in standing and supine positions in patients with varicose veins, fulfilling inclusion and exclusion criteria. Presence or absence of SFJ and SPJ incompetence was assessed.Results: Mean age was 41.99 ± 11.08 years with 36 (51.43%) patients between 36-50 years. Mean duration of disease was 6.33 ± 2.29 months while 47 (67.14%) patients had symptoms for more than 6 months at the time of presentation. Occupation wise, 40 (57.14%) patients were field workers while 30 (42.86%) were office and domestic workers. Isolated SFJ, SPJ and combined junction incompetence were found in 27 (38.57%), 20 (28.57%) and 23 (32.86%) patients respectively. Both SFJ and SPJ incompetence were more in obese patients (78.6% and 71.4% respectively) as compared to non-obese patients.Conclusion: Frequency of SFJ incompetence was more than SPJ incompetence on DUS. Obesity, male gender and prolonged motionless standing predispose to the development of varicose veins. Preventive measures and early diagnosis can decrease disease burden.